The Effect of Train Noise on Comfort Perception and Adaptive Behavior of Urban Café Visitors - Ladina At-Qadar Supriyadi; Popi Puspitasari (Jurnal Ilmiah Global Education, 2026)
Cafes located near railway lines face the challenge of environmental disturbances that can potentially affect the comfort and behavior of users. This study aims to analyze the influence of disturbance levels on the comfort perceptions and adaptive behavior of cafe visitors and employees. The study was conducted at a café in South Jakarta, approximately 40 meters from an active railway line. The research method used a quantitative, descriptive, explanatory approach through field disturbance measurements using a sound level meter and a Likert-based user perception survey. The study showed that disturbance levels in the outdoor area of the café consistently met the recommended comfort threshold, while the indoor area experienced a decrease in sound intensity but remained in the moderate category. However, visitors' perceptions of discomfort remained at low to moderate levels, accompanied by the emergence of adaptive behaviors such as selecting seating areas, adjusting speaking volume, and tolerating short disturbance durations. These findings indicate that train disturbances influence user comfort and behavior, but these effects are moderated by the spatial context and individual adaptability. This research has important implications for cafe design in areas exposed to rail transportation disturbances.